Assessment Instrument of Critical Thinking Skills for Student on Light Interaction with Organisms - Tariza Fairuz (Jurnal Studi Guru dan Pembelajaran, 2021)
Critical thinking skills are one of the skills needed in the 21st century. These skills can be developed and measured in science learning. This study aimed to produce an assessment instrument that can be used to measure critical thinking skills of junior high school students. This assessment instrument was developed in the multiple choice test. The stages of development include a preliminary study, preparation of item questions, test of content validity by experts and empiric validity, and reliability test. A total of 60 junior high school students in Tebing Tinggi became the research sample. This assessment instrument consists of five aspects of critical thinking skills, basic clarification, basic support, inference, advance clarification, and strategy and tactics. 7 of the 25 items are valid with high criteria, 11 are valid with medium criteria and 7 others are valid with low criteria. Reliability test used the Kuder-Richardson (KR-20) approach and the results are reliable with high criteria. The analysis showed that the developed critical thinking skills of junior high school students on the theme of light interaction with organisms.